Depositional Events and Their Records - An Introduction - G. Einsele; S.K. Chough; T. Shiki (Ikatan Ahli Geologi Indonesia, 1998)
Event deposits of some lateral extent as defined here occur almost in all types of sedimentary basins. They reflect either locals, intra-basinal processes, or they are associated with regional or global mechanisms. Some types of event beds, such as sediment gravity flows, sandy and muddy turbidites, are common and usually well preserved. They make up large proportions of basin fills, whereas others (e.g., tsunami deposits and in-situ earthquake structures) appear to be less frequent or rare in the geological record. Volume, frequency, and facies of event deposits are controlled by several processes: pre-event sediment accumulation, triggering and transport mechanism, and mode of final deposition.